2017
DOI: 10.1002/elan.201600735
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Determination of Ciprofloxacin in Physiological Fluids Using Carbon Paste and Nano‐Composite Carbon Paste Electrodes

Abstract: Nano‐composite carbon paste and simple carbon paste based potentiometric sensors were constructed and used for determination of ciprofloxacin at different pH values. Sensors were formulated utilizing graphite, suitable plasticizer, cirprofloxacinium‐phosphotungstate, as well as a highly lipophilic cation‐exchanger, sodium tetrakis(trifluoromethyl)phenyl borate. Effect of the incorporation of multi‐walled carbon nanotubes (MWCNTs) on the response characteristics of the prepared sensors was investigated. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Five tablets of each type were well‐grounded and the amount equivalent to one tablet was dissolved in 0.1 M HCl to enhance solubility, warmed, and filtered to 25 mL with buffer. The PG concentration in these solutions was determined using direct potentiometry by using the calibration curve for determination of unknown concentration [41], and by the reference spectrophotometric method [42]. The recovery and statistical calculations were performed on three measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five tablets of each type were well‐grounded and the amount equivalent to one tablet was dissolved in 0.1 M HCl to enhance solubility, warmed, and filtered to 25 mL with buffer. The PG concentration in these solutions was determined using direct potentiometry by using the calibration curve for determination of unknown concentration [41], and by the reference spectrophotometric method [42]. The recovery and statistical calculations were performed on three measurements.…”
Section: Methodsmentioning
confidence: 99%
“…PG in the different pharmaceutical preparations Diabetonorm ® (45 and 15 mg) was determined with sensor 4 applying direct potentiometry. The results were compared to those obtained by a reference spectrophotometric method [42], and it was very accurate and precise as ensured by recovery values and statistical calculations, Table 7. Comparing the characteristics of constructed sensor 4 to those of the previously reported in the literature (Table 8), significant improvements in a LDR, DL, and selectivity have been achieved by more than two orders of magnitudes in some cases.…”
Section: Determination Of Pg In Pharmaceutical Preparationsmentioning
confidence: 99%
“…However, the sensor super-Nernstian response at pH 2.2 can be caused by the H + -interference [57,58]. Abdel-Haleem et al and Psomas reported that the best pH for potentiometric measurement of LF is 4.1 due to its existence in its monocationic form in the highest ratio with the coexistence of minimum amount of other LF species [31][32][33]; this also was reported for ciprofloxacin [57]. At pH = 4.1, LF + form dominates, and the sensors sub-Nernstian responses in Table 2 is due to the presence of other LF forms (LF 2+ and LF ± ), and due to the H-bond formation [57,58].…”
Section: Effect Of Phmentioning
confidence: 99%
“…Over the years, a range of detection techniques like spectrophotometry [14], capillary electrophoresis [15], chromatography [16] and electrochemical techniques [17] are being used for the determination of ciprofloxacin in aqueous samples. But most of these methods require several time-consuming steps, complex instrumentation and trained personnel.…”
Section: Introductionmentioning
confidence: 99%